Structural and optical analysis of GaN and InxGa1-xN photodetectors fabricated by PEALD on silicon - D. Tepatzi-Xahuentitla; D. Cortes-Salinas; D.A. Granada-Ramírez; Y. Panecatl Bernal; M. Pérez-González; S.A. Tomás; A.A. Durán-Ledezma; Salvador Alcantara-Iniesta; M.L. Gómez-Herrera; J.G. Mendoza-Alvarez; J. Alvarado (Results in Engineering)
The optical, structural, morphological and chemical properties of Gallium nitride (GaN) and Indium Gallium nitride (InxGa1-xN) thin films grown on Si (100) by plasma-assisted atomic layer deposition (PEALD) technique at a temperature of 300°C. X-ray diffraction (XRD) was performed, obtaining polycrystalline films with hexagonal phase to corroborate the obtaining of the materials. In addition, Atomic Force Microscopy (AFM) analysis showed surface roughness, Rrms and Ra values of 2.4 and 1.97 nm for GaN, and 5 and 1.8 nm for InxGa1-xN, respectively. Ultraviolet-visible (UV–Vis) spectroscopic analysis revealed that the band gap energy is 3.44 eV for GaN and 3.15 eV for InxGa1-xN. Both materials were compositionally analyzed by Secondary ion mass spectrometry (SIMS) and X-ray photoelectron spectroscopy (XPS), obtaining a homogeneous distribution of the elements Ga, In, and N, but indicating the formation of indium and nitrogen oxides. Finally, as photodetectors, the GaN/Si and InxGa1-xN/Si devices were evaluated with their photoresponse showing a high response to visible light, good stability and low fall/rise times (GaN: τRise = 0.06 s, τFall = 0.35 s InxGa1-xN: τRise = 0.2 s, τFall = 0.22 s). The peak responsivity was observed at 350 nm for GaN and at 400 nm for InxGa1-xN, indicating a redshift in the spectral response caused by higher indium content in the ternary alloy.These devices were fabricated using uniform nanometric films on silicon, aiming for Complementary Metal-Oxide-Semiconductor (CMOS) compatibility.